High Port Count Hybrid Wavelength Switched TDMA (WS-TDMA) Optical Switch for Data Centers - Funnell, Adam; Benjamin, Joshua; Ballani, Hitesh; Costa, Paolo; Watts, Philip; Thomsen, Benn (Optical Fiber Communication Conference (OFC'16), 2016)
A WS-TDMA optical switch fabric scalable to 1024 ports is demonstrated. Fast tunable (<200ns) transceivers using bipolar encoded transmission and coherent reception enable wavelength switching and TDMA over a passive star network for low latency packet level switching.